THE APPLICATION OF THE COMMUNICATIVE METHOD (COMMUNICATIVE LANGUAGE TEACHING) IN ARABIC LANGUAGE LEARNING FOR BEGINNER STUDENTS - Siti Rahmah; Asmaul Husna; Ana Sofia (STAI Nusantara Kota Banda Aceh, 2026)
The Communicative Method or Communicative Language Teaching (CLT) is a language teaching approach that emphasizes language ability as a means of communication. In the context of Arabic language learning for first-semester students (beginners), this method is considered relevant as it addresses low learning motivation, limited vocabulary mastery, and students’ lack of confidence. This article aims to examine the concepts, principles, and implementation of the communicative method in Arabic language learning for first-year students of the Islamic Economic Law Program at UIN Ar-Raniry. The research method employed is a library study by analyzing various literature sources related to CLT and Arabic language teaching. The results of the study indicate that the communicative method is effective in increasing students’ active participation, speaking confidence, and mastery of basic Arabic language skills in a contextual and functional manner.